Features Of Predictions Before Dental Intervention Taking into Account the Psych emotional State of The Patient - Khazratov Alisher Isamiddinovich; Kamariddinzoda Malikabonu Kamariddinovna (Zien Journals, 2021)
A person is powerless in the face of pain. Every year dentists are fed to reach new heights in the field of pain relief. Despite the fact that anesthesiology is increasingly used in the practice of dentists. Anesthesia used in stationary dental operations does not always allow the desired effectiveness of pain relief to be achieved. One of the reasons for this is the significant psych emotional stress of patients in the preoperative period, which leads to inadequate neuro-somatic reactions of patients to surgical trauma, a change in the feeling of pain. This causes the need for preoperative sedative preparation of patients, providing increased local anesthesia and protecting the patient's psyche from emotional trauma. Currently, a significant number of drugs and drug preparation regimens have been proposed, but none of the proposed means of premedication provides complete fearlessness for all patients without exception, which is possibly due to different individual sensitive patients and drugs. Therefore, the search and study of new means of premeditation is currently necessary and relevant
Keywords: Premedication; dental intervention; psych emotional state; anxiety